2013
DOI: 10.1155/2013/524165
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and Time-Dependent Apoptosis Induced by Avian H9N2 Influenza Virus in Human Cells

Abstract: To understand human response to avian H9N2 influenza, we investigated the effects of the viral infection on A549, HepG2, and HeLa cells at low and high MOIs. To identify virus-host interplay, expression of Mx and NP genes was measured in the cells supernatants. Cell viability and apoptosis were evaluated by MTT assay, DNA fragmentation, and florescent staining. The virus titration and NP gene transcript levels indicate lower susceptibility of HeLa cell to H9N2 replication than other cells. Although H9N2 did pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The host utilizes apoptosis to eliminate influenza A virus by removing virus-infected cells, while viruses can modulate apoptosis for their effective replication and survival [26][27][28][29]. Previous studies have shown that the H9N2 virus induces apoptosis mainly via the mitochondrial pathway in human alveolar epithelial cells [20], and NS1 from H9N2 virus can induce death receptor-mediated apoptosis in chicken macrophages [19]. This prompted us to investigate if the NS1 protein of the novel avian H7N9 influenza A virus can also induce apoptosis in human cells, like its closely-related H9N2 virus, or the NS1 protein of H9N2 in chicken cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host utilizes apoptosis to eliminate influenza A virus by removing virus-infected cells, while viruses can modulate apoptosis for their effective replication and survival [26][27][28][29]. Previous studies have shown that the H9N2 virus induces apoptosis mainly via the mitochondrial pathway in human alveolar epithelial cells [20], and NS1 from H9N2 virus can induce death receptor-mediated apoptosis in chicken macrophages [19]. This prompted us to investigate if the NS1 protein of the novel avian H7N9 influenza A virus can also induce apoptosis in human cells, like its closely-related H9N2 virus, or the NS1 protein of H9N2 in chicken cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that NS1 derived from low pathogenicity H9N2 virus can induce apoptosis in chicken macrophages via the Fas/(FasL)-mediated pathway [19], while in human alveolar epithelial cells, H9N2 virus-induced apoptosis proceeds via the death receptor and mitochondrial pathways in parallel [20]. Although the NS1 gene of the novel H7N9 influenza A virus is derived from the closely-related avian H9N2 virus, several amino acids in NS1 protein of this novel H7N9 influenza A virus has changed (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The highly virulent H5N1 virus induced apoptosis in mammalian alveolar epithelial cells and chicken cells resulted in the deregulation of adaptive immune responses (20,21). The low pathogenic H9N2 virus can induce apoptosis in chicken macrophages by the Fas/(FasL)-mediated extrinsic pathway (18,19) and human alveolar epithelial cells in a time and dose-dependent manner (11). The widespread prevalence of H9N2 subtype in the Middle East region (6,31) and isolation of high lethally H9N2 for mice (8) …”
Section: Discussionmentioning
confidence: 99%
“…Several studies on interaction between influenza viruses and hosts revealed that the infection causes apoptosis or programmed cell death in natural hosts. A variety of host and viral factors are involved in induction of apoptosis that may depend on the cell type (8)(9)(10)(11)(12). The regulation of some host apoptotic factors like cysteinyl-aspartatekinases (caspases) activation interacts with influenza virus replication and pathogenicity (13,14).…”
Section: Introduction Nfluenza Virus a (Iav) Belongs To Thementioning
confidence: 99%
“…The A549 cell line, which originated from human airway epithelial cells, was found susceptible to a strain of H9N2 influenza viruses that we screened (unpublished data). In addition to this, A549 cell line has been used for H9N2 in vitro studies (Lee et al, 2010; Shahsavandi et al, 2013; Hamidreza et al, 2016). Therefore, the A549 cell line was selected for the present proteomic study.…”
Section: Introductionmentioning
confidence: 99%